Cross-Cultural Translation of the Chinese Version of Pain Care Quality Surveys (C-PainCQ) - Jia-Wen Guo; Hui-Ying Chiang; Susan L. Beck (JMIR Publications, 2020)
Health disparities in pain care continue to exist among non-English-speaking Chinese-Americans. The Pain Care Quality © (PainCQ) surveys, a valid instrument measuring the quality of pain care from the patient's perspective, is available only in English currently. This study generated a Chinese version of the PainCQ (C-PainCQ) following a cross-cultural translation approach to address health equity in pain care. A multicultural, bilingual expert team produced a good quality, prefinal version of C-PainCQ. Chinese speaking patients (n = 55) evaluated conceptual and content equivalence while bilingual participants (n = 13) reviewed semantic equivalence of C-PainCQ items. Feedback from participants, including adding a new item related to education on medication compliance, was used to revise the tool. This C-PainCQ is ready for future research to examine the reliability and construct validity with a large sample of Chinese-speaking patients.